The Collaboration Between The Department of Transportation and PT Transjakarta in Developing Public Transportation System - Maylisa Damayanti; Zulmasyhur Zulmasyhur (Universitas Sultan Ageng Tirtayasa, 2024)
This study examines the collaborative efforts between the Department of Transportation Jakarta and Transjakarta to modernize the public transportation system within the southern precincts of Jakarta City. Employing a qualitative descriptive analytical approach, data for this research was garnered through interviews and on-site observations. The study found that the collaboration was successful because there were very few conflicts, and diverse stakeholders actively participated in solving problems together. It's saying that these factors were key indicators of the collaboration's success. A noteworthy impediment surfaced in the form of budgetary constraints, adversely impacting endeavors to revamp public transportation. The research recommends a viable remedy by proposing the introduction of new travel routes and optimizing the utilization of existing budgets. It emphasizes the importance of collaboration in achieving these improvements, highlighting how working together effectively can address challenges and yield positive outcomes.